Partisanship and Fiscal Policy in Economic Unions: Evidence from US States - Carlino, Gerald; Drautzburg, Thorsten; Inman, Robert; Zarra, Nicholas (American Economic Review, 2023)
Partisanship of state governors affects the efficacy of US federal fiscal policy. Using close election data, we find partisan differences in the marginal propensity to spend federal intergovernmental transfers: Republican governors spend less than Democratic governors. Correspondingly, Republican-led states have lower debt, (delayed) lower taxes, and initially lower economic activity. A New Keynesian model of partisan states in a monetary union implies sizable aggregate effects: The intergovernmental transfer impact multiplier rises by 0.58 if Republican governors spend like Democratic governors, but due to delayed tax cuts, the long-run multiplier is higher with more Republican governors, generating an intertemporal policy trade-off. (JEL D72, E12, E62, H71, H72, H74, H77)